1993
DOI: 10.1113/expphysiol.1993.sp003690
|View full text |Cite
|
Sign up to set email alerts
|

Changes in voltage‐operated calcium channels modify ethanol withdrawal hyperexcitability in mouse hippocampal slices

Abstract: SUMMARYMeasurements of hippocampal excitability were made from area CAl of isolated mouse hippocampal slices, prepared after chronic ethanol treatment in vivo, and the effects of the stereoisomers of the dihydropyridine Bay K 8644, that act at calcium channels, were investigated. The decrease in the threshold stimulation required to produce a single population spike, the leftward shift in the population spike input-output curves, and the increase in population spike amplitude, that were seen during ethanol wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Our findings in the Ca v 1.2 HKO mice as well as those obtained with DHP fit well with data from some earlier reports studying the role of L-type calcium channels by means of DHP (Whittington and Little, 1993;Pineda et al, 1998;Chen et al, 2005). For example, the DHP L-type channel blockers nifedipine Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings in the Ca v 1.2 HKO mice as well as those obtained with DHP fit well with data from some earlier reports studying the role of L-type calcium channels by means of DHP (Whittington and Little, 1993;Pineda et al, 1998;Chen et al, 2005). For example, the DHP L-type channel blockers nifedipine Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The role of L-type calcium channels in generating repetitive firing of neurons in the CNS is not clear. Studies with pharmacological tools yielded contradictory results (Moyer et al, 1992;Whittington and Little, 1993;Pineda et al, 1998;Chen et al, 2005) and, importantly, do not allow to discriminate between individual members of the L-type channel family. Here, we examined the intrinsic excitability of CA1 pyramidal cells from control mice and mice with the Ca v 1.2 gene inactivated in principal hippocampal neurons.…”
Section: Introductionmentioning
confidence: 95%
“…Besides several other factors (e.g. functional deficits of GABA receptors and increased VGCC function [77,212]), the NMDARs are major contributors to the increased glutamate release during alcohol withdrawal since in the brain of ethanol-dependent rats, the extracellular concentration of glutamate shows a transient, NMDAR mediated increase after cessation of ethanol intake and these changes are time-locked to the behavioural signs of ethanol withdrawal [44,53,183]. This enhanced glutamate release may contribute to the further shift towards the excitatory dominance in the CNS after ethanol withdrawal [184].…”
Section: Consequences Of Increased Nmdar Functionmentioning
confidence: 99%
“…Ca 2ϩ current density was normalized and expressed as the percentage of the current evoked in the presence of vehicle. tion of L-type VGCC function, are involved in dependence on other central nervous system depressants such as ethanol, barbiturates, and morphine, as well as stimulants, including nicotine (Whittington and Little, 1993;Pourmotabbed et al, 1998;Rabbani and Little, 1999;Katsura et al, 2002). The finding that chronic, but not acute, benzodiazepine administration enhances HVA Ca 2ϩ currents suggests that a similar effect may occur in hippocampal CA1 pyramidal neurons associated with benzodiazepine withdrawal symptoms (Van Sickle et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…VGCCs have been implicated in mediating synaptic plasticity associated with dependence on a wide range of central nervous system stimulants and depressants (Whittington and Little, 1993;Pourmotabbed et al, 1998;Rabbani and Little, 1999;Katsura et al, 2002Katsura et al, , 2005Katsura et al, , 2007Watson and Little, 2002;Rajadhyaksha and Kosofsky, 2005). Specifically, previous studies from our laboratory have demonstrated an enhancement of ␣-amino-3-hydroxy-5-methylisoxasole-4-propionic acid receptor (AMPAR) synaptic currents in hippocampal CA1 neurons Song et al, 2007), which was associated with anxiety-like behavior in benzodiazepine-withdrawn rats (Van Sickle et al, 2004;Xiang and Tietz, 2007).…”
mentioning
confidence: 99%